THE MODERN SYSTEM OF NON-MATERIAL STIMULATION OF PERSONNEL OF THE ORGANIZATION - A. Mitrofanovа (Вестник университета)
The most important condition of increase of efficiency of activity of companies is staff incentives. And if financial incentives are investigated well enough, the question of non-material motivation of staff requires further study. This problem devoted this article. The author paid special attention to the areas of non-financial incentives as awareness and promotion of free time. The results of the analysis of domestic and foreign experience of non-material incentives of personnel. Specific recommendations on the organization of flexible work schedules of employees, and to develop a corporate portal for employees with the aim of increasing awareness and involvement of staff in the management of the company.